PARADIGMA FILSAFAT EKONOMI SYARIAH SEBAGAI SUATU SOLUSI KEHIDUPAN MANUSIA - Wan Shalah Sabila; Annisa Fitri Awaliyah; Fitrah khairuna Ulfa Lubis (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This research aims to examine in depth the philosophical paradigm of Islamic economics as an integral solution to human life. This research intends to understand more deeply the basic principles that underlie Islamic economics, including key concepts such as justice, equality, and sustainability. This research uses the literature research method, an approach based on the analysis of written works, both published and unpublished. This method was chosen because this research aims to examine and analyze the Islamic economic philosophy paradigm as a solution to human life. The Islamic economic philosophy paradigm can be considered as a relevant and effective solution in facing contemporary economic and social challenges.